A bivariate multilevel analysis of Portuguese students - Faria, Susana (2020)
In this work, we illustrate how to perform a bivariate multilevel analysis in the complex setting of large-scale assessment surveys. The purpose of this study was to identify a relationship between students' mathematics and science test scores and the characteristics of students and schools themselves. Data on about 7325 Portuguese students and 246 Portuguese schools who participated in PISA-2015 were used to accomplish our objectives. The results obtained by this approach are in line with the existing research: the index of the socioeconomic status of the student, being a male student, the average index of the socioeconomic status of the student in school positively influence the student's performance in mathematics and science. On the other hand, the grade repetition had a negative influence on the performance of the Portuguese student in Mathematics and Science.